Evidence for a differential contribution of early perceptual and late cognitive processes during encoding to episodic memory impairment in schizophrenia. (4th July 2017) - Green, Amity E.; Fitzgerald, Paul B.; Johnston, Patrick J.; Nathan, Pradeep J.; Kulkarni, Jayashri; Croft, Rodney J.
Abstract: Objectives: Schizophrenia is characterised by significant episodic memory impairment that is thought to be related to problems with encoding, however the neuro-functional mechanisms underlying these deficits are not well understood. The present study used a subsequent recognition memory paradigm and event-related potentials (ERPs) to investigate temporal aspects of episodic memory encoding deficits in schizophrenia. Methods: Electroencephalographic data was recorded in 24 patients and 19 healthy controls whilst participants categorised single words as pleasant/unpleasant. ERPs were generated to subsequently recognised versus unrecognised words on the basis of a forced-choice recognition memory task. Subsequent memory effects were examined with the late positive component (LPP). Group differences in N1, P2, N400 and LPP were examined for words correctly recognised. Results: Patients performed more poorly than controls on the recognition task. During encoding patients had significantly reduced N400 and LPP amplitudes than controls. LPP amplitude correlated with task performance however amplitudes did not differ between patients and controls as a function of subsequent memory. No significant differences in N1 or P2 amplitude or latency were observed. Conclusions: The present results indicate that early sensory processes are intact and dysfunctional higher order cognitive processes during encoding are contributing to episodic memory impairments in schizophrenia.